Small-pad Resistive Micromegas: Comparison of patterned embedded resistors and DLC based spark protection systems. (April 2020) - Iodice, M.; Alviggi, M.; Camerlingo, M.T.; Canale, V.; Della Pietra, M.; Di Donato, C.; Iengo, P.; Petrucci, F.; Sekhniaidze, G.
Abstract: We present the development of resistive Micromegas aiming at operation under high rates, up to tens MHz/cm 2, focusing on the optimisation of the spark protection resistive layer and the miniaturisation of the readout elements. Several Micromegas detectors have been built with an anode plane matrix of 48x16 rectangular readout pads, each pad 0.8x2.8 mm 2 . The detectors differ for the spark protection resistive schemes being realised with the following techniques: a pad-patterned embedded resistor by screen printing, and uniform DLC (Diamond Like Carbon structure) layers. Characterisation and performance studies of the detectors have been carried out by means of radioactive sources, X-Rays, and test beam. A comparison of the performance obtained with the different resistive layouts is presented, in particular focusing on the response under high irradiation and high rate exposure.